Mass absorption and mass energy transfer coefficients for 0.4–10MeV gamma rays in elemental solids and gases - Gurler, Orhan; Gundogdu, O.; Yalcin, S.; Oz, H. (Elsevier BV, 2009)
The mass energy absorption, the mass energy transfer and mass absorption coefficients have been widely used for problems and applications involving dose calculations. Direct measurements of the coefficients are difficult, and theoretical computations are usually employed. In this paper, analytical equations are presented for determining the mass energy transfer and mass absorption coefficients for gamma rays with an incident energy range between 0.4 and 10 MeV in nitrogen, silicon, carbon, copper and sodium iodide. The mass absorption and mass energy transfer coefficients for gamma rays were calculated, and the results obtained were compared with the values reported in the literature.
Keywords: Silicon; Energy Transfer; Gamma Rays; Nitrogen; Sodium Iodide; Elements; Carbon; Copper; Absorption; 7. Clean energy